2012
DOI: 10.4111/kju.2012.53.11.790
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Shock Wave Rate for Shock Wave Lithotripsy in Urolithiasis Treatment: A Prospective Randomized Study

Abstract: PurposeWe aimed to compare the effects of a fast shock wave rate (120 shocks per minute) and a slow shock wave rate (60 shocks per minute) on the shock wave lithotripsy (SWL) success rate, patient's pain tolerance, and complications.Materials and MethodsA total of 165 patients with radiopaque renal pelvis or upper ureter stones were included in the study. Patients were classified by use of a random numbers table. Group I (81 patients) received 60 shock waves per minute and group II (84 patients) received 120 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…In all studies, SFRs were higher when shock waves were administered at a slower rate, reaching a statistically significant difference (p < 0.05) in one study [53]. One study showed that the mean number of SWL sessions required was reduced in patients undergoing fast SWL (p = 0.021) [51]. The other study showed that duration of procedure was significantly reduced in patients undergoing fast SWL compared to slow SWL (p < 0.001) [53].…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 98%
See 1 more Smart Citation
“…In all studies, SFRs were higher when shock waves were administered at a slower rate, reaching a statistically significant difference (p < 0.05) in one study [53]. One study showed that the mean number of SWL sessions required was reduced in patients undergoing fast SWL (p = 0.021) [51]. The other study showed that duration of procedure was significantly reduced in patients undergoing fast SWL compared to slow SWL (p < 0.001) [53].…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 98%
“…In one study, there was no significant difference in the achieved SFR at 2 wk [50], whereas in the other study, these rates were improved by treating the patient prone rather than supine (90.6% vs 88.3%, p < 0.05) [49]. Three studies looked at whether the administered shock rate affected SFRs [51,53,56]. In all studies, SFRs were higher when shock waves were administered at a slower rate, reaching a statistically significant difference (p < 0.05) in one study [53].…”
Section: Swl Prone Versus Swl Supinementioning
confidence: 99%
“…When treating the stones located in the renal pelvis, SWL had a highest SFR (80–88 per cent), but the SFR decreased when treating upper pole stones (73 per cent), midpolar stones (69 per cent) and lower pole stones (63 per cent) . When treating multiple renal stones with SWL, SFR dropped to 50–55 per cent .…”
Section: Discussionmentioning
confidence: 98%
“…Exclusion criteria included the following: (1) contraindications to SWL, (2) multiple UC, (3) febrile urinary tract infections, (4) a single kidney, (5) nonfunctioning kidney, (6) azotemia (creatinine > 1.8 mg/dl), (7) ureteral strictures, (8) severe hydronephrosis on imaging studies, (9) a past history of cystine stones, and (10) ureteral stent insertion before SWL due to colic.…”
Section: Patients and Study Designmentioning
confidence: 99%